THE IMPLEMENTATION OF PRODUCT PROFITABILITY ANALISYS STRATEGY IN INCREASING BUSINESS PERFORMANCE (CASE ILLUSTRATION: A GARMENT INDUSTRY IN BANDUNG) - Elizabeth T Manurung; Arthur Purboyo; Thomas Kurniawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
More severe competition in business of today globalization, coupled with the scorching of economic condition, is demanding companies to constantly seek out ways to preserve their excellence performance, meaning 'doing the right things right' in order that they can achieve optimal performance. The deceptive belief that by increasing sales volume companies can increase their profit has caused them to accept orders over products and consequently increase costs no matter what difference each order made in activities consumption. The concept is based on idea 'The smaller the production volume, the smaller the cost'. Accordingly, this idea leads to overstated calculation ofprofit in ABC (activity based costing), product cost calculation will differ with activities. Accordingly, this gives accurate and complete information about cost for activities and cost for every product. This way, managements know which product(s) is (are) profitable, which part of the operation is (are) efficient, how to make sound strategy to create maximum profit. Finally, this work will end up with an analysis over which product is profitable for a garment industry in Bandung: sweater, cardinal (long pants), or vestKeywords: business competition, activity based costing, traditional cost system, product profitabilit